Achieving the tobacco endgame: evidence on the hardening hypothesis from repeated cross-sectional studies in New Zealand 2008–2014. Issue 4 (5th July 2016) - Edwards, Richard; Tu, Danny; Newcombe, Rhiannon; Holland, Kate; Walton, Darren
Abstract : Introduction: The hardening hypothesis proposes that as smoking prevalence declines the proportion of 'hardcore' or 'hardened' smokers will increase. The possible constructs of hardening include reduced motivation to quit, increased levels of addiction, increased levels of disadvantage and reduced quit rates among continuing smokers. Most previous studies have investigated only a single facet of the hypothesis. We used data from a national population monitor to test the hypothesis using measures across all four hardening constructs. Methods: We analysed data from a biennial population-based survey of New Zealand adults (aged 15 years+) from 2008 to 2014. Data were collected through face-to-face computer-assisted personal interviews. Results: During a period of reducing smoking prevalence, there were no statistically significant changes in indicators of hardening including the proportion of smokers who were unmotivated to quit, unable to quit despite repeated attempts or receiving state benefits or on a low income. Quit rates did not change significantly over the study period. For 2014 versus 2008, the OR for recent (within last 1–12 months) quitting was 1.14 (95% CI 0.53 to 2.46) and for sustained (within previous 13–24 months) quitting was 1.88 (95% CI 0.78 to 4.54). Conclusions: This study provides evidence that robust tobacco control strategies that result in substantial declines in smoking prevalence are not accompanied by the hypothesised increase in 'hardcore' or 'hardened' smokers who are more addicted and less motivated and able to quit. The findings suggest that there is no need for substantial change in approach to achieve New Zealand's Smokefree 2025 goal on the grounds that the smoker population is becoming increasingly hardened.